1999
DOI: 10.1006/viro.1999.9967
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mouse Mammary Tumor Virus Envelope Protein Does Not Prevent Superinfection In Vivo or In Vitro

Abstract: Inbred mice expressing endogenous mouse mammary tumor virus envelope proteins can be infected with exogenous virus, and the mammary tumors that develop in these mice usually have many proviruses integrated in their genomes, indicating that this virus is not subject to receptor interference. We show here that transgenic mice expressing an exogenous mouse mammary tumor virus (C3H) envelope protein can still be infected with this virus. Moreover, cultured mammary gland cells expressing the mouse mammary tumor vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In some superinfecting scenarios, a reduction of viral envelope-receptor affinity prevents efficient superinfection resistance, thereby allowing superinfection to occur (9,19). One estimate of envelope-receptor affinity is the rapidity of virion binding to the cells.…”
Section: Vol 82 2008 Eiav Superinfection and Superinfection Resistamentioning
confidence: 99%
See 2 more Smart Citations
“…In some superinfecting scenarios, a reduction of viral envelope-receptor affinity prevents efficient superinfection resistance, thereby allowing superinfection to occur (9,19). One estimate of envelope-receptor affinity is the rapidity of virion binding to the cells.…”
Section: Vol 82 2008 Eiav Superinfection and Superinfection Resistamentioning
confidence: 99%
“…In addition, two accessory proteins, Nef and Vpu, interact and remove CD4 from the plasma membrane (12,16,26,29). Superinfection resistance mechanisms of other retroviruses, such as mouse mammary tumor virus and foamy viruses, are independent of the envelope (3,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have clearly demonstrated that MMTV is transported to the mammary gland by lymphocytes and that infected B and T cells can release MMTV particles (6)(7)(8)(9). Because removal of the draining LN after virus infection abolished the neutralizing Ab responses, we were able to address the viral spread to lymphoid and nonlymphoid compartments in the absence of neutralizing Abs.…”
Section: Viral Infection and Tumor Development In The Absence Of Neutmentioning
confidence: 99%
“…Exemption from Institutional Review Board review was obtained from the NIH Office of Human Subjects Research. Monoclonal a-gp52 hybridoma supernatant BL6 5D, as well as caprine sera from goats hyperimmunised with MMTV (a-MMTV) or with gp52 (polyclonal a-gp52), served as positive control reagents (Dzuris et al, 1999;Purdy et al, 2003). In a central repository, three aliquots of each of these reagents (neat, 1 : 10 and 1 : 100 dilutions in defibrinated plasma (Basematrix, BBIBiotech Inc., Frederick, MD, USA)) were put into vials identical to the human sera.…”
Section: Patients and Controlsmentioning
confidence: 99%